Perioperative Transcutaneous Tibial Nerve Stimulation to Reduce Postoperative Ileus After Colorectal Resection: A Pilot Study. Issue 9 (September 2018) - Venara, Aurélien; Bougard, Marie; Mucci, Stéphanie; Lemoult, Annabelle; Le Naoures, Paul; Darsonval, Astrid; Barbieux, Julien; Neunlist, Michel; Hamy, Antoine P.
Abstract : BACKGROUND: Postoperative ileus involves an inflammatory pathway characterized by an increase of inflammation mediators in the colon wall; this could probably be prevented by sacral nerve neuromodulation. The posterior tibial nerve can be stimulated electrically to mimic neuromodulation. OBJECTIVE: The aims of this study were to assess the efficacy of transcutaneous posterior tibial nerve stimulation in reducing the delay in GI motility recovery, to assess the safety of posterior tibial nerve stimulation in a perioperative setting, and to assess the efficacy of posterior tibial nerve stimulation in reducing the occurrence of postoperative ileus. DESIGN: This was a preliminary randomized controlled study. SETTINGS: This study was conducted in 1 academic hospital in France. PATIENTS: Forty patients undergoing an elective colectomy were included and randomly assigned into 2 groups, posterior tibial nerve stimulation or placebo, according to the side of colectomy and the surgical access size. INTERVENTION: Perioperative posterior tibial nerve stimulation or placebo was performed 3 times per day according to the randomly assigned group. MAIN OUTCOME MEASURES: Delay in GI motility recovery (passage of stool and tolerance of solid food) was measured. RESULTS: Of the 40 patients included, 34 were included in the final analysis, in which 2 patients in the placebo group were allocated the incorrect device. The 6 other patients were secondarily excluded because of protocol deviation. In the intention-to-treat analysis, the mean delay in GI motility recovery was 3.6 and 3.11 days (in the placebo and tibial nerve stimulation groups; p = 0.60). Occurrence of postoperative ileus was not significantly higher in the placebo group (35.3% vs 17.6%; p = 0.42). In the per-protocol analysis, we observed the same trends except for the occurrence of postoperative ileus, which was significantly higher in the placebo group ( p = 0.045). Tolerance to posterior tibial nerve stimulation was good, and all of the patients completed the protocol. LIMITATIONS: The amplitude of stimulation is set according to patient sensation, so some patients could have been aware of their group. In addition there were some inherent limitations because of the preliminary nature of the study and several deviations from the protocol. CONCLUSIONS: Posterior tibial nerve stimulation was safe in a perioperative setting and had a potential effect on GI motility recovery. The results of this study will be useful for sample size calculations in a larger prospective randomized trial. SeeVideo Abstract athttp://links.lww.com/DCR/A708 .